Tourism and new rurality: on the road to social sustainability - Palafox-Muñoz, Alejandro (2015)
International Organizations have proposed sustainability as an alternative to overcome the effects of neoliberalism; however, results in reducing poverty and improving the quality of life have expanded. The new rurality drives diversification of activities to generate income that allows conserving the mode and relations of production framed in its social organization. Tourism adds to the traditional activities of communities founded on the use and conservation of resources, it is an instrument of rural development which, through active participation of communities, enabling them to promote and strengthen their collective and regional identity. This document presents the effects of the capitalist mode of production, and two approaches of the new rurality, where the Community part contributes to improving the social sustainability of rural communities.